Knowledge purification of Kindergarten Children - Manar Muntasser Shaalaan; Altaf Yaseen Khithr (College of Education for Women, 2023)
The research is concerned with the problems of knowledge purification of kindergarten children by verifying its aims, identifying of knowledge purification among the first level of kindergarten children and the second level of kindergarten children, and the differences between the males and females in the variable of knowledge purification. The research community included the children in the state and private kindergartens in Baghdad governorate, on its two sides, Karkh and Rusafa, for the six districts for the academic year 2022-2023. After making the knowledge purification test according to the scientific steps of test constructions, the test has been presented to a group of experts specialized in the field of kindergarten to ascertain the validity of the test items and to calculate the discrimination, the items difficulty, and the test stability according to Kuder Richardson. The final form of the knowledge purification test consists of 13 items of two alternatives Yes, No with scores 1-0 that the highest score for the test is 13 and the lowest score is zero with a hypothetical medium of 6.5. Fnally, the test was applied to a sample of 400 children from state and private kindergartens who were selected randomly. The results were that the children have a good degree of knowledge purification, there is no differences between the first level of kindergarten children and the second level of kindergarten children and no differences between males and females in the knowledge purification variable. Then the two researchers put forwards a number of recommendations and suggestions: 1.The Iraqi Ministry of Education should be interested in adopting the useful scientific experiences for the child in the kindergartens, so that the knowledge purification is selected in a best possible way. • There should be a relationship between the knowledge purification and the academic achievement of the kindergarten child parents.